Layered Perforated Steel Armour - Wiesław Stępniak; Wiesław Habaj; Paweł Podgórzak (Problemy Mechatroniki)
The article presents design and testing methods of layered perforated steel armour developed by HTK Company and Military Institute of Armament Technology, which can be used as add-on-armour of vehicles and other light armoured objects. Armour configurations differing in number and thickness of layers (steel plates), shape and spacing of holes (perforations), distance (dilatation) between individual layers and assembly of layers were tested. Layered armours were fired in accordance with STANAG 4569 and AEP-55 protection levels III and IV.